Modern Principles of Diagnosis of Cardiovascular Diseases - Makhamadhojayeva Mukhabbat Abdusatarovna; Adilova Nargiza Oripovna (Genius Journals, 2023)
This article provides information about the modern principles of diagnosis of cardiovascular diseases.
Keywords: Heart; artery; atherosclerosis; hypertension